Biocomposites From Biodegradables Polymer And Modified Oil Palm Empty Fruit Bunch Fiber - Ahmad, Siti Nur Afifi (2009)

(untitled)
Natural fiber reinforced composites using thermoplastic such as polypropylene and polyethylene as a matrix produced partially biodegradable composites. In order to produce totally biodegradable composites or green composites, poly(ε-caprolactone) was used as the matrix. However the hydrophilic nature of oil palm empty fruit bunch fiber (natural fiber) affects negatively its adhesion to hydrophobic polymer matrix, thus to improve the compatibility of both components a cross-linker, poly(Nvinylpyrrolidone) and electron beam radiation have been proposed. The composites of OPEFB:PCL were prepared by melt blending technique using Haake Internal Mixer. The effect on the amount PVP and doses of electron beam irradiation on mechanical properties of OPEFB:PCL were studied. The properties of OPEFB:PCL composites were improved by addition of 1% by weight of PVP and irradiated with 10 kGy of electron beam. The FTIR spectra indicate a slight interaction between OPEFB with PCL after adding PVP and irradiation in agreement with the significant improvement of mechanical properties. The tensile strength of OPEFB:PCL without PVP and treatment is 10.3 MPa whereas after addition of PVP and treatment the tensile strength increased to 16.7 MPa indicating good stress transfer from OPEFB to PCL matrix. Addition of PVP and treatment with electron beam also increase the flexural strength and modulus to 24.32 and 8.69 % respectively. The impact strength is also slightly increased with PVP and irradiation which is about 2.28 %. From XRD patterns, it can be inferred that the amorphous phase of the composites is slightly increased after adding PVP whereas no significant change was observed after irradiation. Thermal properties of the composites were studied by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). From the results, there is also no significant improvement observed for thermal stability of the composites. The surface morphology of the facture surface obtained from tensile test shows no fiber pull out indicating interaction between the OPEFB and PCL after addition of PVP and irradiation. The environmental degradation behavior on the physical properties of OPEFB:PCL composites has been studied with special reference to the influence of ageing conditions like treatment with water and soil degradation. From water uptake analysis, it can be inferred that the composites become more water resistant after the irradiation. The soil burial test was carried out in 3 months, indicates that irradiation and fiber loading tend to promote degradation of the composites.